Possible Paternal Hepatitis B Virus Infection with Different Clinical Courses between Siblings: A Report of Two Cases - Yoshiaki Sasaki; Hiroki Kajino (Case Reports in Hepatology)
The incidence of hepatitis B virus (HBV) infection is expected to decrease in the future owing to the preventive measures adopted against mother-to-child transmission of HBV and implementation of universal HBV vaccination for children. However, no countermeasure has been established against horizontal infection in nonvaccinated children. We report the case of two siblings who had different clinical courses of possible paternal HBV infection. The younger sibling developed acute hepatitis, whereas the older sibling was an asymptomatic HBV carrier. To eradicate HBV, HBV vaccination of all children and HBV infection screening of fathers and other family members should be encouraged.